Influence of ion size effects on the electrokinetics of aqueous salt-free colloids in alternating electric fields - Carrique-Fernández, Félix; Ruiz-Reina, Emilio; Arroyo Roldán, Francisco José; Delgado Mora, Ángel Vicente (American Physical Society (APS), 2020)
Electrokinetics is an important tool for the characterization of colloids because of its sensitivity to the electrical properties of particle-solution interfaces. Its rigorous description may require inclusion of the effects of finite size of chemical species in the theoretical models, and, particularly in the case of salt-free (no external salt added) aqueous colloids, also consideration of water dissociation and possible carbon dioxide contamination in the aqueous solution. A new ac electrokinetic model is presented for concentrated salt-free spherical colloids for arbitrary characteristics of the particles and aqueous solution, including finite size effects of chemical species by appropriate modifications of the chemical reaction equations to include such non-ideal aspects. The numerical solution of the electrokinetic equations in an alternating electric field has also been carried out by using a realistic non-equilibrium scenario accounting for association-dissociation processes in the chemical reactions. The results demonstrate the importance of including finite size effects in the electrokinetic response of the colloid, mainly at high frequencies of the electric field, and for highly charged colloids. Findings of previous models for point-like ions or for ideal salt-free colloids including finite ion size effects are recovered with the present model, for the appropriate limiting conditions.
Keywords: AC electrokinetics; dielectric dispersion; electrophoresis; finite ion size; salt-free systems